SIALOCHEMISTRY- A NON-INVASIVE DIAGNOSTIC TOOL IN SYSTEMIC DISEASES. - SUKANYA. D; DR. SUBHA.M (International Journal of Pharma and Bio Sciences, 2013)
Saliva, a non- invasive bio-fluid secreted by the salivary glands not only lubricates the oral cavity but also has antibacterial, antifungal and antiviral properties and also regulates pH. It contains mucin, protein, salt, starch and hormones. It can be easily collected and can be used as a diagnostic fluid in assessing most of the systemic disease. Also they play a major role in monitoring drug level and forensic odontology.